Availability of forest residues and potential for energy production in temperate forests in El Salto, Durango - Villela-Suárez, Juan Martín; Aguirre-Calderón, Oscar Alberto; Treviño-Garza, Eduardo Javier; Vargas-Larreta, Benedicto (Instituto de Ecología, A.C., 2018)
Forest harvest residues are a source of renewable energyfor which their use has not yet been considered on a large scale in Mexico and for whose quantification, increasingly accurate assessments are required. In this study equations were developed to estimate the volume of forest residues in order to assess the regional availability of logging residues and their potential for electricity generation and CO2 emission displacement in the forest region El Salto, Durango. The methodology consisted of three steps: i) the forest management programs of 20 ejidos were revised to calculate the available total volume; (ii) 2156 trees from the harvest areas were felled and its volume estimated to develop tree-level residues equations; and (iii) the volume of waste was converted to tons of biomass using the wood density values each group species, and then this value was transformed to units of electrical energy. Due to these species often constitute mixed stands with the same silvicultural treatments and rotation age, differences among species in the volume residues equations were examined using the nonlinear extra sum of squares method. The model parameters were signiﬁcantly different among species. The amount of forest residues at the tree scale was higher in the Quercus species, while the amount of forest residues was higher, per cut cycle, in Pinus species. Around 31 000 Mg year-1 of forest residues can be used to generate approximately 65.6 GW year-1, considering the use of a technology with a minimum efficiency of 40%,